2016
DOI: 10.1002/masy.201500161
|View full text |Cite
|
Sign up to set email alerts
|

Recycling of Post‐Consumer HDPE Drug Packaging with Banana Pseudostem Fiber

Abstract: As the life expectancy of the population increases, the quantity of solid waste produced has also risen. There is therefore a clear need to recycle materials, particularly polymers, and it is very important to reduce the time taken for materials to degrade after they have been discarded. The objective of this study was to develop a composite material from a mixture of waste drug packaging made from HDPE and fiber from the pseudostems of banana plants. A series of experiments were conducted to determine the cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Research has shown that the increase in untreated short fiber content will actually decrease the tensile strength most likely caused by fibers being below the required critical fiber length. 12,13 By treating the fibers, the interfacial bond strength is increased, therefore decreasing the critical fiber length. Thus, by treating the fibers, there is an increase in the tensile strength with increased short fiber content as shown by Prasad et al 14 The same increasing strength trend can be achieved using longer fibers.…”
Section: Natural Fiber Compositesmentioning
confidence: 99%
“…Research has shown that the increase in untreated short fiber content will actually decrease the tensile strength most likely caused by fibers being below the required critical fiber length. 12,13 By treating the fibers, the interfacial bond strength is increased, therefore decreasing the critical fiber length. Thus, by treating the fibers, there is an increase in the tensile strength with increased short fiber content as shown by Prasad et al 14 The same increasing strength trend can be achieved using longer fibers.…”
Section: Natural Fiber Compositesmentioning
confidence: 99%
“…26,27 It is essential that the material is rigorously cleaned to remove any debris that can negatively affect the properties/quality of final products. A granulation process or pelletizing process is the second stage 28 where the rHDPE is remelted in an extruder and granules/pellets or films are produced. Fillers/additives/fibers can be introduced into the rHDPE.…”
Section: Introductionmentioning
confidence: 99%